ANTECEDENT FINANCIAL PERFORMANCE OF BAITUL MAL WAT TAMWIL (BMT): STUDY IN BMT BINAMA SEMARANG - Zahra, Milla Himmatuz; Wijayanti, Provita (Universitas Islam Negeri (UIN) Walisongo Semarang, 2019)
Purpose - BMT is established as an Islamic micro-finance which gives the loans to the middle-low society. A good financial performance describes a good BMT condition to distribute their own loans. This research is a case study of BMT Binama Semarang City during 2009-2013.Method - The kind of data used are secondary data, monthly financial reports for balance statement, profit and loss, and collectability. The instrument of financial performance was measured based on stable, stable?enough, less-stable, and unstable quality using the variables of capitalizing structure, productive asset quality, liquidity, cost efficiency, capitalizing efficiency, economic rentability, and self-capital rentability. The data were analyzed by using multiple linear regression analyses.Result - The research found that financial performance of BMT in 5 years was stable-enough, caused by losing condition on 2010. The result of multiple linear regression showed that there were only two independent variables which had significant affect, they are: cost efficiency and economic rentability. Economic rentability gives more significant role in financial performance of BMT.Implication - The results showed that the financial performance of BMT Binama Semarang City was quite healthy. This quite healthy condition can be raised to be healthy through efforts to focus improvements on variables that show low scoring, namely cost efficiency and economic profitability.Originality - This study focuses on the financial performance of BMT Binama Semarang City.